Barium Defaecating Proctography: Experience from a Tertiary Referral Center - Wan Chew, Cindy Sze; Yeap, Elaine Ee-Min; O’Dwyer, Patrick J. (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Objective Pelvic floor dysfunction (PFD) is a major health care problem predominately affecting the elderly female. It impairs quality of life and patients increasingly expect a solution. Barium defaecating proctography (BDP) is frequently used in the assessment of patients with PFD. The aim of this study was to present our findings from BDP and to look at the proportion of patients who went on to have surgery following their investigations.Methods All patients who underwent BDP in a tertiary referral center were identified retrospectively from the computerized radiology information system. Demographic data and radiologic findings were extracted. Data regarding those who had surgery were retrieved from the anonymized patient registry.Results A total of 671 patients had a BDP during the study period. The main symptoms investigated were obstructed defecation or chronic constipation (64%). Complete barium evacuation was observed in 70% of the patients, while 17% were noted to have incomplete and 13% no evacuation. A large rectocele (>5 cm) was noted in 38% while nearly 5% had frank prolapse. There was no significant association between a rectocele and any of the presenting symptoms. Seventy-eight (12%) patients went on to have operation, of which 17 (22%) had multiple procedures. Three patients ended up with a permanent stoma.Conclusion BDP contributes to decision making in patients with PFD. However, results need to be interpreted with caution and in conjunction with other tests and clinical examination to maintain a low rate of operation and reduce the risk of adverse outcomes for these patients.
Keywords: barium defaecating proctogram; pelvic floor dysfunction; long term follow-up